An Approach to the Synthesis of Functionalized Polycyclic Aromatic Hydrocarbons. Issue 27 (9th August 2013) - Little, Mark; Lan, He; Raftery, James; Morrison, John J.; McDouall, Joseph J. W.; Yeates, Stephen G.; Quayle, Peter
Abstract: The application of a new benzannulation reaction for the regiocontrolled synthesis of functionalized chrysenes is reported. The initial benzannulation and the subsequent halogen displacement reactions are both highly regiospecific, which thereby enables the regiocontrolled synthesis of a variety of 4, 10‐disubstituted chrysenes from commercially available 1, 5‐dihydroxynaphthalene. Abstract : 4, 10‐Dichlorochrysene, which is itself readily available from 1, 5‐dihydroxynaphthalene, undergoes facile displacement reactions with a variety of nucleophiles to afford 4, 10‐disubstituted chrysene derivatives.